Оцінка ефективності експрес-гістологічного дослідження у визначенні обсягу дисекції за папілярного раку щитоподібної залози - Смоляр, В. А.; Шаповал, Н. О.; Гузь, О. О.; Хоперія, В. Г. (Clinical Endocrinology and Endocrine Surgery, 2013)
This study retrospectively evaluated the efficacy of frozen section of lymph nodes in the neck during surgery for papillary thyroid cancer in order to determine the amount of dissection. The frequency of metastasis to regional lymph nodes was 35,6%. The diagnostic sensitivity, specificity and efficiency of frozen section neck lymph nodes during surgery for papillary thyroid cancer were 91,7%, 85,7% and 87.8% respectively.